Histone N-alpha terminal modifications: genome regulation at the tip of the tail - Demetriadou, Christina (Epigenetics Chromatin, 2020)
Histone proteins are decorated with numerous post-(PTMs) or co-(CTMs) translational modifications mainly on their unstructured tails, but also on their globular domain. For many decades research on histone modifications has been focused almost solely on the biological role of modifications occurring at the side-chain of internal amino acid residues. In contrast, modifications on the terminal N-alpha amino group of histones—despite being highly abundant and evolutionarily conserved—have been largely overlooked. This oversight has been due to the fact that these marks were being considered inert until recently, serving no regulatory functions. However, during the past few years accumulating evidence has drawn attention towards the importance of chemical marks added at the very N-terminal tip of histones and unveiled their role in key biological processes including aging and carcinogenesis. Further elucidation of the molecular mechanisms through which these modifications are regulated and by which they act to influence chromatin dynamics and DNA-based processes like transcription is expected to enlighten our understanding of their emerging role in controlling cellular physiology and contribution to human disease. In this review, we clarify the difference between N-alpha terminal (Nt) and internal (In) histone modifications; provide an overview of the different types of known histone Nt-marks and the associated histone N-terminal transferases (NTTs); and explore how they function to shape gene expression, chromatin architecture and cellular phenotypes.